2011
DOI: 10.1016/j.polymer.2011.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical properties of semi-degradable Poly(β-amino ester)-co-methyl methacrylate networks under simulated physiological conditions

Abstract: Poly(β-amino ester) networks are being explored for biomedical applications, but they may lack the mechanical properties necessary for long term implantation. The objective of this study is to evaluate the effect of adding methyl methacrylate on networks' mechanical properties under simulated physiological conditions. The networks were synthesized in two parts: (1) a biodegradable crosslinker was formed from a diacrylate and amine, (2) and then varying concentrations of methyl methacrylate were added prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The samples tested under accelerated conditions disintegrated over a span of 20 weeks, where the highest timepoints experienced massive disintegration. The use of PEGDA‐based PBAE crosslinkers allows for rapid swelling and degradation; however, if a more hydrophobic PBAE was used, the swelling and degradation rate would be severely decreased 52. Further tailoring of degradation rate can be achieved either by mixing diacrylates within the PBAE composition or lower concentrations of PBAE 36…”
Section: Discussionmentioning
confidence: 99%
“…The samples tested under accelerated conditions disintegrated over a span of 20 weeks, where the highest timepoints experienced massive disintegration. The use of PEGDA‐based PBAE crosslinkers allows for rapid swelling and degradation; however, if a more hydrophobic PBAE was used, the swelling and degradation rate would be severely decreased 52. Further tailoring of degradation rate can be achieved either by mixing diacrylates within the PBAE composition or lower concentrations of PBAE 36…”
Section: Discussionmentioning
confidence: 99%
“…The PBAE macromers were mixed with MMA (45 wt% PBAE macromer: 55 wt% MMA) and 0.5 wt% Irgacure 2959. This solution was photopolymerized for 45 minutes under a UVP Blakray lamp (~10mW/cm 2 ) [32]. A Bruker Vector 22 FTIR with Pike Technologies Miracle ATR attachment with ZnSe crystal was used to characterize the chemical structure of the networks after photopolymerization.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have separately examined the combinatorial characterization of PBAE networks and the thermo-mechanical properties of (meth)acrylates [18, 29]. Previous work has also demonstrated that by mixing with varying amounts of methyl methacrylate (MMA), the thermo-mechanical properties of hydrophobic PBAE networks can be tuned to increase Tg, increase toughness, and maintain a rubbery state [32]. However, the relationships between hydrophilicity and thermo-mechanical behavior have yet to be assessed throughout the degradation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 As can be seen from the results, LPBAEU-T2 and LPBAEU-A2 networks (D:A ratio of 1.4:1) showed the highest Tg values because of the reduction in chain mobility of these highly crosslinked structures. [50][51][52]…”
Section: Structural Characterization Of Lpbaeu Macromers and Networkmentioning
confidence: 99%